Hepatic solitary fibrous tumor: Report of a rare case - Sushma Patra; Mukul Vij; K Venugopal; Mohamed Rela (Wolters Kluwer Medknow Publications, 2012)
Solitary fibrous tumor (SFT) of the liver is an extremely rare neoplasm of mesenchymal origin. In the English literature, less than 40 cases of SFTs of the liver have been reported. The present case concerns a 34-year-old female who presented to us with complaint of dyspepsia. On examination, there was hepatomegaly. On ultrasound examination, an SOL in the liver was detected. Large tumor measuring 14.5 × 10 × 8 cm was resected. Microscopic evaluation of the tumor showed a well-circumscribed, low to moderately cellular tumor demonstrating spindle- and fibroblast-like cells within the collagenous stroma. Immunohistochemistry revealed diffuse strong cytoplasmic immunopositivity of CD34, Bcl2, and vimentin. A diagnosis of a benign SFT was given. The patient remained well 4 years after surgery. SFT is a rare mesenchymal neoplasm that occasionally involves the liver in adult patients. Most SFTs are benign, but some may have malignant histological features. With less than 40 reported cases in the literature, little can be said regarding its natural history or the benefits of adjuvant radio chemotherapy. Complete surgical resection remains the cornerstone of its treatment.